Comparison of Fentanyl and Midazolam for the Sedation of Infants Under Mechanical Ventilation; A Randomized Clinical Trial - Bita Najafian; Bahareh Esmaeili; Mohammad Hossein Khosravi (Baqiyatallah University of Medical Sciences, 2017)
Background: Neonatal respiratory distress syndrome (NRDS), a life-threatening pulmonary disorder, involves 1% of all deliveries worldwide. Shallow breathing causes restlessness in infants, which itself affects pulmonary function; thus, sedative medications are used to preserve better pulmonary function. There are different opinions about the benefits and superiority of these drugs. Objective: The study purposed to assess and compare the effects of fentanyl and midazolam on the required time of mechanical ventilation in infants with respiratory distress syndrome (RDS). Methods: In this randomized clinical trial, 60 infants with RDS were randomly allocated to 2 groups (30 infants each); the first group underwent sedation with midazolam (0.1 mg/kg), and the second group received 0.5 mcg/kg of fentanyl during ventilation. The duration of hospitalization, required time of ventilation, drug complications, feeding intolerance, as well as pneumothorax incidence and need for re-intubation were recorded and compared between the 2 groups. Results: Eventually, 60 infants (45 male and 15 female) with a mean gestational age of 37.13±1.22 weeks in the midazolam group and 36.73±1.50 weeks in the fentanyl group underwent analysis (P value=0.449). Infants in the midazolam group had a mean length of stay of 11.96 ± 3.41 days, while mean length of stay was 10.36±3.57 days for infants in the fentanyl group (P value=0.039). Mean duration of mechanical ventilation was 4.6±2.14 days in the midazolam group and 4.06±2.04 days in the fentanyl group (P value=0.252). Conclusion: The findings suggest that midazolam is a more suitable medication for the sedation of infants under mechanical ventilation in comparison with fentanyl; however, its side effects, such as apnea, pneumonia, and seizure, should be considered.